2001
DOI: 10.3184/030823401103169847
|View full text |Cite
|
Sign up to set email alerts
|

Substituted N-Salicylidene β-Aminoalcohols: Preparation and use as Chiral Ligands in Enantioselective Sulfoxidation and Conjugate Addition

Abstract: A high yielding synthesis of optically active 3,5-disubstituted salicylidene β-amino alcohols (6) is described. The catalytic use of D or L- N-(3-phenyl-5-nitrosalicylidene)valinol in enantioselective sulfoxidation (H2O2 / VO(acac)2) gives up to 95% e.e. Asymmetric conjugate addition of thiophenol to 2-cyclohexen-1-one catalysed by Ti(OPr- i)4 and 6 leads to maximum 31% e.e. in the product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 14 publications
0
28
0
Order By: Relevance
“…Methods of preparation of the hydrazides 4b-c and aldehydes of choice 6a-b, 6d-f, 7a-b, and 7d-f were adapted from the original literature [54][55][56][57][58][59][60][61][62][63][64]. 4-Methoxy-and 3-hydroxybenzoic acid hydrazides 4b and 4c were prepared in 67-85% yields from the appropriate benzoic acid methyl esters 8b and 8c and hydrazine monohydrate following a literature procedure [63].…”
Section: Syntheses and Characterizationsmentioning
confidence: 99%
“…Methods of preparation of the hydrazides 4b-c and aldehydes of choice 6a-b, 6d-f, 7a-b, and 7d-f were adapted from the original literature [54][55][56][57][58][59][60][61][62][63][64]. 4-Methoxy-and 3-hydroxybenzoic acid hydrazides 4b and 4c were prepared in 67-85% yields from the appropriate benzoic acid methyl esters 8b and 8c and hydrazine monohydrate following a literature procedure [63].…”
Section: Syntheses and Characterizationsmentioning
confidence: 99%
“…[6] Skarzewski et al introduced Schiff bases with a phenyl substituent at C 3 of salicylaldehyde. [7] Anson et al reported that a vanadium-chiral Schiff base complex derived from 3,5-diiodosalicylaldehyde and (S)-t-leucinol was effective in the vanadium-catalyzed oxidation of alkyl aryl sulfides. [8] Ahn described the application of sterically hindered chiral Schiff base ligands that were prepared from chiral t-leucinol and aldehydes derived from binol for the oxidation of sulfides.…”
Section: Introductionmentioning
confidence: 99%
“…Bolm first reported the famous vanadium catalyst system prepared in situ from VO(acac) 2 and substituted with the salicylidene derivative ( S )‐ tert ‐leucinol in 1995, which effectively catalyzed the oxidation of sulfides to sulfoxides using hydrogen peroxide as the oxidant with good enantioselectivity (up to 80% ee ) 7. Since then many optimizations have been carried out on the basis of this protocol including: (i) the use of other amino alcohols for the preparation of Schiff bases as chiral ligands,8 (ii) ( S )‐ tert ‐leucinol‐based Schiff bases modified with various aromatic aldehydes,6,8a,9 (iii) the manner of H 2 O 2 addition and the use of additives,10 (iv) the method of oxidation/kinetic resolution 11…”
Section: Methodsmentioning
confidence: 99%